UTILIZATION OF THE ANDROID APPLICATION “BOCESTING” IN ENHANCING KNOWLEDGE FOR MOTHERS OF CHILDREN UNDER FIVE YEARS ABOUT STUNTING PREVENTION - Safitri, Tiyara; Dewi Mey Lestanti Mukodri, (International Journal of Social Science, 2024)
The most common health problem is malnutrition, called stunting. In the province of Riau Islands in 2020, 7.2% of cases were distributed among seven districts/cities. One attempt to address nutritional problems in young children is to approach health education using the Android method. Continuing previous research on nutritional therapies as delayed prevention in the news, using brochure media to stop prevention (Bocesting), implementation of Bocesting has a knowledge-increasing effect compared to the dissemination method. Based on this, the author is interested in researching brochure prevention of stunting (Bocesting) based android application as a learning environment in improving maternal nutritional behavior and nutritional status news, so that in Riau Islands community a special field of work in Puskesmas Kampung Bugi complexity. village Bugis District, Tanjungpinang City to analyze the differences in the effect of education on the prevention of stunting using a media leaflet and an Android-based application to improve maternal nutritional behavior and nutritional news to prevent news-induced stunting events.